Study on cryogenic mechanical properties between superconducting wires and resins for MRI superconducting magnet. (April 2021) - Sun, Wentao; Wu, Zhixiong; Huang, Chuanjun; Zhang, Hengcheng; Shen, Fuzhi; Huang, Rongjin; Gong, Linghui; Zhou, Yuan; Li, Laifeng
Highlights: The epoxy resin has a low viscosity and long pot life. At 77 K, the epoxy resin offers high tensile strength and modulus. The superconducting magnet exhibits high shear and compressive strength at 77 K. Abstract: Superconducting magnet is a key component in magnetic resonance imaging (MRI). In general, vacuum pressure impregnation (VPI) technology is used for insulating system of the superconducting magnet. Performance of the superconducting magnets is affected by the adhesion strength between superconducting wires and resins at cryogenic temperature. In this study, experimental superconducting coil was prepared by modified bisphenol-A type epoxy resin and the VPI technology. Tensile, shear, and compressive properties of the samples cut from the superconducting coil were measured at both room temperature (RT) and liquid nitrogen temperature (77 K), and the bonding properties between the superconducting wire and the resin were discussed. The results show that the resin exhibits low viscosity, long pot life and higher mechanical strength, and it is suitable for impregnating superconducting magnets by VPI technology. Moreover, the shear and compressive strength of the impregnated superconducting magnet at 77 K are significantly higher than that at room temperature, with the increase of 132% in radial compressive strength, 170% in axial compressive strength, 63% in radial shear strength and 70% in axial shear strength, respectively. This study provides references for the design of insulation for superconducting magnet system and the manufacture of insulating materials for MRI superconducting magnets.